2022
DOI: 10.1007/s00228-022-03364-5
|View full text |Cite
|
Sign up to set email alerts
|

Co-prescription of metoprolol and CYP2D6-inhibiting antidepressants before and after implementation of an optimized drug interaction database in Norway

Abstract: Purpose To compare the co-prescription of metoprolol and potent CYP2D6-inhibiting antidepressants before and during a 10-year period after implementation of an optimized drug interaction database into clinical decision support systems in Norway. Methods The study was a retrospective, cross-sequential nationwide analysis of drug-dispensing data retrieved from the Norwegian Prescription Database over a 1-year period before (2007) and two 1-year periods after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The DPWG has also developed numerous recommendations for more than 40 CYP2D6-metabolized medications (Figure 1). Several are published [10][11][12][13][14] and those not included in publications are provided on the Pharmacogenomics Knowledgebase (PharmGKB; https://www.pharm gkb.org). Moreover, consensus has been reached between the CPIC and DPWG in terms of diplotype to phenotype translation.…”
Section: How Far We Have Advanced With Cyp2d6 Pharm Aco Gen Etics Cur...mentioning
confidence: 99%
“…The DPWG has also developed numerous recommendations for more than 40 CYP2D6-metabolized medications (Figure 1). Several are published [10][11][12][13][14] and those not included in publications are provided on the Pharmacogenomics Knowledgebase (PharmGKB; https://www.pharm gkb.org). Moreover, consensus has been reached between the CPIC and DPWG in terms of diplotype to phenotype translation.…”
Section: How Far We Have Advanced With Cyp2d6 Pharm Aco Gen Etics Cur...mentioning
confidence: 99%
“…For example, administration of paroxetine increased plasma concentrations of metoprolol by more than five-fold, and severe bradycardia and atrioventricular block have been reported in patients taking both drugs. 17 The objectives of the present study were to investigate the interaction of PLP with cytochrome P450 enzymes and to determine the pharmacokinetic alteration of metoprolol resulting from pretreatment with PLP. methorphan, 4-hydroxytolbutamide, 4-nitrophenol, and omeprazole were purchased from Sigma-Aldrich Chemical (St. Louis, MO).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Studies have shown that the plasma concentration of metoprolol can increase by multiple fold and even cause bradycardia after taking drugs with CYP2D6 inhibitory properties. For example, administration of paroxetine increased plasma concentrations of metoprolol by more than five-fold, and severe bradycardia and atrioventricular block have been reported in patients taking both drugs …”
Section: Introductionmentioning
confidence: 99%